Soil black carbon decline following deforestation and farming in karst rocky desertification Southwest Guangxi, China - Zhang, Denan; Teng, Qiumei; Huang, Kechao; Shen, Yuyi; Sun, Yingjie; Xu, Guangping; Shi, Hao; Zhang, Yanzhao (Frontiers in Environmental Science, 2026)
Black carbon (BC) is produced by the incomplete combustion of biomass and fossil fuels. After deposition in soils, BC forms a relatively stable carbon pool that contributes to long-term carbon sequestration. Understand the effects of land use on soil BC is critical for accurately interpreting the role of BC in the carbon cycle of karst areas. This study investigated the distribution characteristics of organic carbon (OC), BC, char, soot, and soil physicochemical properties within the 0–40 cm soil profiles of secondary forest, shrub, farmland, and wasteland in a rocky desertification area of Guangxi Province, a typical karst region in Southwest China. A combination of soot/char separation and δ13CBC isotope analysis was used to identify the sources of BC in these soils. The result show that average soil BC content was highest in secondary forests (7.20 g/kg), followed by shrub (5.85 g/kg), farmland (3.64 g/kg), and wasteland (3.38 g/kg). BC showed a positive correlation with OC, char, soot, soil nitrogen, phosphorus, and potassium, and a negative correlation with bulk density. Among BC components, char accounted for a greater proportion than soot, and the heavy fraction of OC exhibited a higher BC concentration than the light fraction. Overall, the BC content was primarily derived from C3 plant combustion, vehicle exhaust emissions, and fossil fuel use in agricultural production activities. Vegetation restoration improved soil BC levels and promoted OC sequestration, while thereby enhancing soil carbon stability.